Self-Regulated Learning in Distance Education to Foster Twenty-First-Century Skills - Mahayanti, Ni Wayan Surya; Suwastini, Ni Komang Arie; Dantes, Gede Rasben; Suryandani, Putu Dinia; Minxia, Zhu (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2023)
AbstractThis research aimed to fill the existing research gap by examining the relationship between SRL and the 21st Century skills in distance education, highlighting the significance of understanding how these competencies intersect to enhance remote learning outcomes. The research design of this study is a systematic literature review adopting George’s (2008) model. The data were collected through assigning codes, developing themes, comparing and conducting close scrutiny of the codes and themes using 48 articles as secondary data sources. After the data were collected, qualitative analysis was done. The findings of this article have mainly addressed the positive light of twenty-first-century learning. The 21st Century skills fall into three categories: learning, literacy, and life skills. Students’ SRL directly affects their self-efficacy towards distance learning, while other factors, such as readiness and motivation, are also very contributive. The component of self-regulation concerns students ' active learning and taking a reflective role in their cognition, behaviour, emotions, and motivation of academic functioning to fulfill the requirement of twenty-first-century skills. Distance education potentially provides an environment that helps students manage their way of thinking in a way aligned with the 21st Century's needs. Furthermore, within Islamic studies, this research contributes to an emerging discourse on how SRL strategies can be tailored to cultivate critical Islamic perspectives and knowledge acquisition in online educational settings.AbstrakPenelitian ini bertujuan untuk mengisi kesenjangan penelitian yang ada dengan menguji hubungan antara SRL dan keterampilan abad ke-21 dalam konteks pendidikan jarak jauh, menyoroti pentingnya memahami bagaimana kompetensi-kompetensi ini berpotongan untuk meningkatkan hasil pembelajaran jarak jauh. Desain penelitian ini adalah tinjauan literatur sistematis yang mengadopsi model George (2008) dan data dikumpulkan melalui pemberian kode, pengembangan tema, perbandingan, dan melakukan pemeriksaan teliti terhadap kode dan tema menggunakan 48 artikel sebagai sumber data sekunder. Setelah data terkumpul, analisis kualitatif dilakukan. Temuan artikel ini sebagian besar mengarah pada pandangan positif tentang pembelajaran abad ke-21. Keterampilan abad ke-21 terbagi menjadi tiga kategori yaitu keterampilan belajar, keterampilan literasi, dan keterampilan kehidupan. SRL mahasiswa secara langsung memengaruhi efikasi diri mereka terhadap pembelajaran jarak jauh, sementara faktor-faktor lain seperti kesiapan dan motivasi mahasiswa juga sangat berkontribusi. Komponen pengaturan diri yang berpusat pada mahasiswa untuk melakukan pembelajaran aktif dan mengambil peran reflektif dalam kognisi, perilaku, emosi, dan motivasi fungsional akademik untuk memenuhi persyaratan keterampilan abad ke-21. Pendidikan jarak jauh berpotensi memberikan lingkungan yang membantu mahasiswa untuk mengelola cara berpikir mereka sesuai dengan kebutuhan abad ke-21. Selain itu, dalam bidang studi Islam, penelitian ini berkontribusi pada wacana yang muncul tentang bagaimana strategi SRL dapat disesuaikan untuk membudayakan pandangan Islam kritis dan pemerolehan pengetahuan dalam pengaturan pendidikan online.How to Cite: Mahayanti, N.W. S., Suwastini, N.K.A., Dantes, G.R., Suryandani, P.D., & Minxia, Z. (2023). Self-Regulated Learning in Distance Education to Foster Twenty-First-Century Skills. TARBIYA: Journal of Education in Muslim Society, 10(2), 1-26. doi:10.15408/tjems.v10i2.37797.